Negative association between lipoprotein associated phospholipase A2 activity and baroreflex sensitivity in subjects with high normal blood pressure and a positive family history of hypertension - Čelovská, D; Vlčková, K; Gonsorčík, J (Physiological research, 2021)
The relationship between baroreflex sensitivity (BRS) and inflammatory vascular biomarker Lipoprotein associated phospholipase A2 (Lp-PLA2) in subjects with high normal blood pressure (HNBP, prehypertensives) with a positive family history of hypertension (FHH+) and hypertension history free control subjects (FHH-) was evaluated. A total of 24 HNBP participants (age 39.5 ± 2.5 years, 18 male/ 6 female) were studied. 14 HNBP subjects FHH+ were compared to 10 HNBP participants FHH-, being of similar age and body mass index. BRS (ms/mmHg) was determined by the sequence and spectral methods (five-minute non-invasive beat-to-beat recording of blood pressure and RR interval, controlled breathing at a frequency of 0.33 Hz). Venous blood was analyzed for Lp-PLA2 biomarker of vascular inflammation and atherothrombotic activity. A significant negative correlation between spontaneous BRS obtained by both methods and systolic blood pressure (BP) was present (BRS spect r = -0.54, P<0.001, BRS seq r = -0.59, P<0.001). BRS obtained by sequence and spectral methods were reduced in HNBP FHH+ compared to the group of HNBP FHH- (P = 0.0317 BRS seq, P = 0.0395 BRS spect). Lp-PLA2 was significantly higher in HNBP FHH+ compared to FHH- controls (P<0.05). Lp-PLA2 was negatively correlated with BRS obtained by sequence method (r = -0.798, R2 = 0.636, P<0.001) in the HNBP FHH+ subjects. These findings demonstrate that reduced baroreflex sensitivity, as a marker of autonomic dysfunction, is associated with vascular inflammation, predominantly in otherwise healthy participants with a positive family history of hypertension who could predispose to increased risk of hypertension. We conclude that our transversal study suggests that a lowbaroreflex sensitivity could be an early sign of autonomic dysfunction even in the prehypertensive period, and to corroborate these findings, a longitudinal study is needed.
Keywords: dospělí; Baroreflex; hypertenze; Female; autonomní nervový systém; biologické markery; Biomarkers; Autonomic Nervous System; Adult; ženské pohlaví; Predictive Value of Tests; prediktivní hodnota testů; anamnéza; lidé; studie případů a kontrol; 1-Alkyl-2-acetylglycerophosphocholine Esterase; krevní tlak; Risk Factors; Hypertension; Male; Case-Control Studies; rizikové faktory; Medical History Taking; lidé středního věku; baroreflex; mužské pohlaví; Blood Pressure; Middle Aged; 1-alkyl-2-acetylglycerofosfocholinesterasa; Humans